Analisis Pembiayaan Konsumtif Pada Bank BNI Syariah Kantor Cabang Jakarta Timur Dimasa Pandemi - Zulaeha Zulaeha; Danang Choirul Umam (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
Consumptive financing is the most sought after financing by the community to meet secondary needs. The purpose of this study is to describe consumptive financing at Bank BNI Syariah East Jakarta Branch Office during the covid-19 pandemic. This study uses a qualitative descriptive method. The result of this study show that during the covid-19 pandemic, BNI Syariah did not experience a significant decline in profits, even during the pandemic. This has a positive impact on consumer financing. This data is obtained from consumer monitoring on the EFO (Electronic Financing Origination) system